Measuring Cultural Awareness Among Slovene Nursing Student: A Cross-Sectional Study. (January 2021) - Ličen, Sabina; Karnjuš, Igor; Prosen, Mirko
Background: Measurements of nursing students' cultural awareness are needed to evaluate education that intends to improve nurses' cultural competency skills. The purpose of this study was to assess the level of cultural awareness held by undergraduate nursing students.Method: A nonexperimental, cross-sectional design was applied to a purposive sample of 149 undergraduate nursing students. Data were collected based on the Cultural Awareness Scale (CAS).Results: The results show that the nursing students had a moderately high level of cultural awareness for all CAS subscales ( M = 194.0). However, no statistically significant differences were seen between the students' demographic (gender and age) and other data (year of study and religion) related to the overall CAS score ( p > .05).Discussion: Building on the satisfactory results obtained from this study, in the future, both the transcultural nursing contents as well as various strategies for teaching cultural competencies should be carefully evaluated.